58.5k views
1 vote
Solve the Differential equation (x^2 + y^2) dx + (x^2 - xy) dy = 0

User Z Star
by
5.3k points

1 Answer

2 votes

Answer:


(y)/(x)-2ln((y)/(x)+1)=lnx+C

Explanation:

Given differential equation,


(x^2 + y^2) dx + (x^2 - xy) dy = 0


\implies (dy)/(dx)=-(x^2 + y^2)/(x^2 - xy)----(1)

Let y = vx

Differentiating with respect to x,


(dy)/(dx)=v+x(dv)/(dx)

From equation (1),


v+x(dv)/(dx)=-(x^2 + (vx)^2)/(x^2 - x(vx))


v+x(dv)/(dx)=-(x^2 + v^2x^2)/(x^2 - vx^2)


v+x(dv)/(dx)=-(1 + v^2)/(1 - v)


v+x(dv)/(dx)=(1 + v^2)/(v-1)


x(dv)/(dx)=(1 + v^2)/(v-1)-v


x(dv)/(dx)=(1 + v^2-v^2+v)/(v-1)


x(dv)/(dx)=(v+1)/(v-1)


(v-1)/(v+1)dv=(1)/(x)dx

Integrating both sides,


\int{(v-1)/(v+1)}dv=\int{(1)/(x)}dx


\int{(v-1+1-1)/(v+1)}dv=lnx + C


\int{1-(2)/(v+1)}dv=lnx + C


v-2ln(v+1)=lnx+C

Now, y = vx ⇒ v = y/x


\implies (y)/(x)-2ln((y)/(x)+1)=lnx+C

User Iskar Jarak
by
5.8k points